MAKNA AL-QUR'AN DITURUNKAN DALAM TUJUH HURUF - Suarni Suarni (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2017)
The study in this paper is about the meaning and wisdom of the Qur'an is revealed in seven letters. Seven letters have various meanings. Among them are seven languages. Although different in interpreting the seven letters, but the difference is inseparable from the seven faces namely differences in the form of Isim, Fi'il, I'rab, Naqis and Ziyadah, Taqdim and Ta'khir, Tabdil, and the form of Lahjah (dialect). Such diversity is a manifestation of the perfection of the miracles of the Qur'an, which can accommodate various dialects and various ways of reading the Qur'an. Facilitating them to read, memorize and understand the Qur'an is as a lesson of diversity and the revealed of the Qur'an in seven letters.